1-MCP maintains postharvest quality of fresh lotus seeds by modulating ethylene signaling, phenolic metabolism, and starch metabolism - Hongyan Lu; Haizhen Si; Xueting Liu; Qiong Lin; Hongru Liu; Yang Yi; Hongxun Wang; Ting Min (Postharvest Biology and Technology, 2026)

Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Waste mop cloth recycling enables rapid, high-throughput removal of viscous winter oil spills - Min Zhang; Ching-Wen Lou; Kaifang Xie; Hengshu Zhou; Jia-Horng Lin; Guangting Han; Que Chen; Ting Dong (Journal of Hazardous Materials, 2026)

Enzymatic synthesis of a new and bioactive dihydrochalcone: 3,4-dihydroxy-2′,6′-dimethoxy dihydrochalcone - Te-Sheng Chang; Jiumn-Yih Wu; Hsiou-Yu Ding; Tzi-Yuan Wang; Guan-Cheng Liu; Min-Lin Wang; Huei-Ju Ting (Natural Product Research, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Thin film nanocomposite membrane incorporated with sulfonic acid-based HOFs for efficient reverse osmosis desalination - Yu-ting Liu; Zi-yue Tang; Zi-ao Zong; Wan-zhen Wang; Xiao-yin Zhang; Xin-ping Song; Xiang-min Meng; Rijia Lin; Jingwei Hou (Desalination, 2026)

Protective role and mechanism of sonic hedgehog signaling pathway in spinal cord injury - Li Li Yin; Xiao Zhen Ji; Min Tang; Li Hui Chen; Jiu Zhou Lin; Ya Ling Jin; Wei Ting Chen (Molecular & Cellular Toxicology, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Interactive effects of retinal biomarkers and sleep on cognition: longitudinal evidence from community-dwelling older adults - Ting-Wen Chu; Yi-Ting Hsieh; Jeng-Min Chiou; Yao-Lin Liu; Yen-Ching Chen; Jen-Hau Chen (GeroScience, 2026)

Novel metabolic pathway of skatole degradation by Enterococcus hirae IDO5 and its application in swine manure wastewater treatment - Yanzhi Lin; Yanchen Liu; Xianyong Ma; Miao Yu; Yiyan Cui; Guangying Weng; Jing Yu; Ting Rong; Zhichang Liu; Dun Deng; Min Song (Journal of Hazardous Materials, 2026)

Self-cleaning nanofiber membrane for efficient oil-water separation and dye degradation - Hai-chao Bai; Zi-yue Tang; Zi-ao Zong; Xin-ping Song; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Rijia Lin; Jingwei Hou (Journal of Cleaner Production, 2026)

Plasmid-mediated modulation of Listeria monocytogenes biofilm formation via TCS/PTS signaling: Implications for food contamination control - Jing Wang; Hui-Min David Wang; Yang Qu; Ting Lin; Changyan Zhou; Zijie Lin; Yangtai Liu; Zhuosi Li; Qingli Dong; Yujuan Suo (Food Research International, 2026)

Whole-genome sequencing reveals the genetic diversity of Aeromonas from freshwater fish and the presence of novel genomic islands carrying clinically important antimicrobial resistance genes - Xiao-Qin Wang; Ke Wu; Run-Min Kang; Heng Lin; Lu-Ya Liu; Ting Xian; Yi-Zhi Tang; Xin Yang; An-Yun Zhang; Hong-Ning Wang; Chang-Wei Lei (Aquaculture, 2026)

Aldehyde dehydrogenase 2 mitigates acrolein-driven ferroptosis to preserve kidney function - Yu-Ming Kuo; Shiu-Dong Chung; Jui-Ting Chang; Hui-Min Yang; Chieh-Chen Lee; Chih-Ching Lin; Hsiang-Tsui Wang (Environmental Pollution, 2026)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Geotechnical reconnaissance of Hualien Port after the 2024 ML 7.2 hualien earthquake - Hsuan-Chih Yang; Chun-Jia Huang; Yung-Yen Ko; Kuan-Yu Chen; Chi-Chin Tsai; Chun-Hung Lin; Yu Wei Hwang; Min-Chien Chu; Yu-Syuan Jhuo; Yu-Ting Hsueh; Shodai Okano; LeeYi Wang; et al. (Soil Dynamics and Earthquake Engineering, 2025)

Anaerobic Fe(II) bio-oxidation by Cyanidiophyceae to enhance As(III) removal: A novel and efficient biological material toward resilient remediation - Nhu Anh Thi Than; Liang Ching Hsu; Yu-Hsien Chen; Kamonchanok Huangmee; Chun-Chieh Wang; Heng Yi Teah; Yu-Min Tzou; Yen-Lin Cho; Yu-Ting Liu (Chemical Engineering Journal, 2025)

Preparation and characterization of IgY antibody and its application in immunochromatographic assay for bongkrekic acid and its isomer - Bin Wang; Xue-Ming Cao; Ting-Ting Yun; Xiao-Min Liang; Yi-Na Lu; Yu-Xin Zhong; Zhen-Lin Xu (Analytica Chimica Acta, 2025)

A dansyl-quinolinium-based ratiometric fluorescent probe for detecting HSO3-/SO32- in living cells - Feng-Ting Liu; Xian-Fang Liu; Zhi Jin; Bao-Xiang Zhao; Zhao-Min Lin (Analytica Chimica Acta, 2025)

Unrecognized emissions and health risks of intermediate-volatility organic compounds in vehicle cabins: Insights from a nontargeted analytical approach - Haoning Chang; Yajun Wu; Jing Zhang; Dianjia Liu; Yao Zeng; Pengfei Song; Jinsheng Zhang; Yan Liu; Lin Wu; Ting Wang; Hongjun Mao; Jianfei Peng; et al. (Journal of Hazardous Materials, 2025)

Synergistic enhancement of PBAT biodegradation by Purpureocillium lilacinum BA1S: Insights from transcriptomics and functional analyses - Wei-Sung Tseng; Min-Jia Lee; Tzu-Yen Chen; Shih-Shun Lin; Sheng-Lung Chang; Pei-Yin Lin; Ting-Jang Lu; Chi-Te Liu (Journal of Hazardous Materials, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Self-cleaning nanofiber membranes for sustainable dual removal of oils and dyes from wastewater - Hai-chao Bai; Yu-kun Sun; Zi-yue Tang; Zi-ao Zong; Yu-ting Liu; Xiaoyin Zhang; Xin-ping Wang; Xiang-min Meng; Jingwei Hou; Rijia Lin (Chemical Engineering Journal, 2025)

Corrigendum to “Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes” [J Hazard Mater 489 (2025) 137706] - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Collagenases from hepatopancreas and muscle of Litopenaeus vannamei: Purification, characterization and comparison of their behaviors in collagen degradation - Xu-Chen Xiao; Jia-Yin Huang; Yu-Lei Chen; Kai-Yuan Cao; Ru-Qing Yang; Duan-Quan Lin; Shu-Jun Hong; Yu-Ting Yang; Min-Jie Cao (Food Chemistry, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

MiR-218 Exhibits Anti-Leukemia Effects by Targeting CTNND2 in Primary Acute Erythroid Leukemia HEL Cells - Ming-qiang Chu; Ting-juan Zhang; Zi-qi Liu; Qian Yang; Ting-ting Du; Min-jie Zhang; Ye Jin; Yong-jie Cao; Xiang-mei Wen; Zi-jun Xu; Yang-jing Zhao; Jiang Lin; et al. (Cell Biochemistry and Biophysics, 2025)

Methane Index and TEX86 values in cold seep sediments: Implications for paleo-environmental reconstructions - Sze Ling Ho; Yu-Shih Lin; Pei-Ling Wang; Tzu-Ting Chen; Pei-Ting Lee; Hui-Hsin Wang; Tzu-Jung Cheng; Yun-Ju Wang; Chih-Chieh Su; Min-Te Chen (Geochimica et Cosmochimica Acta, 2025)

Sulfur-functionalized sawdust biochar for enhanced cadmium adsorption and environmental remediation: A multidisciplinary approach and density functional theory insights - M.M.M. Ahmed; Chih-Hao Liao; S. Venkatesan; Yu-Ting Liu; Yu-Min Tzou; Shih-Hao Jien; Ming-Chang Lin; Yi-Cheng Hsieh; Ahmed I. Osman (Journal of Environmental Management, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Sulfur-functionalized rice straw biochar for enhanced cadmium sorption: Spectroscopic, kinetic and computational insights - M.M.M. Ahmed; Chih-Hao Liao; Yu-Ting Liu; S. Venkatesan; Yi-Chen Hsieh; H.M. Nail; Hui-Min David Wang; Ming-Chang Lin; Shih-Hao Jien; Yu-min Tzou (Journal of Cleaner Production, 2024)

Effects of Limosilactobacillus reuteri on ruminal microbiota, muscle protein metabolism, and flavor of Sunit lamb - Ting Liu; Maoqin Zhai; Taiwu Zhang; Min Zhang; Chenlei Wang; Yanni Zhang; Yan Duan; Lin Su; Ye Jin; Lina Sun (Food Bioscience, 2024)

Trimetallic-doped carbon nitride achieves chondroitin sulfate degradation via a free radical degradation strategy - Xiao-jun Lin; Meng-ting Chang; Min Cao; Muhammad Sohail; Meng Qiao; Xing Zhang (Carbohydrate Polymers, 2024)

The endonuclease FEN1 mediates activation of STAT3 and facilitates proliferation and metastasis in breast cancer - Min Wu; Xiaoshan Huang; Benmeng Wu; Miaolin Zhu; Yaqin Zhu; Lin Yu; Ting Lan; Jingjing Liu (Molecular Biology Reports, 2024)

Removal of antibiotics from aquaculture wastewater using a continuous flow/EC/PMS coupled system - Lulu Long; Jingrong Li; Ting Hou; Min Liu; Yuhuan Lin; Xingwei Zhu; Chao Chen; Gang Yang; Jingsong He (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Accumulation and bio-oxidation of arsenite mediated by thermoacidophilic Cyanidiales: innate potential biomaterials toward arsenic remediation - Yen-Lin Cho; Yu-Min Tzou; Afifah Assakinah; Nhu Anh Thi Than; Hwan Su Yoon; Seung In Park; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Pei-Yu Huang; Shao-Lun Liu; Yu-Ting Liu (Bioresource Technology, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Thiol-functionalized black carbon as effective and economical materials for Cr(VI) removal: Simultaneous sorption and reduction - Kamonchanok Huangmee; Liang-Ching Hsu; Yu-Min Tzou; Yen-Lin Cho; Chih-Hao Liao; Heng Yi Teah; Yu-Ting Liu (Journal of Environmental Management, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

A highly sensitive ratiometric fluorescent probe for detecting HSO3−/SO32− and viscosity change based on FRET/TICT mechanism - Feng-Ting Liu; Shu-Mei Zhai; Dong-Fang Gao; Shu-Hao Yang; Bao-Xiang Zhao; Zhao-Min Lin (Analytica Chimica Acta, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Ecological and functional differences of abundant and rare sub-communities in wastewater treatment plants across China - Kuo Yang; Wei Liu; Hui-min Lin; Tan Chen; Ting Yang; Bing Zhang; Xianghua Wen (Environmental Research, 2024)

Breaking prolonged sitting increases 24-h physical activity and self-perceived energy levels but does not acutely affect cognition in healthy adults - Feng-Chih Kuo; Yun-Ting Lin; Ting-Yu Chueh; Yu-Kai Chang; Tsung-Min Hung; Yung-Chih Chen (European Journal of Applied Physiology, 2024)

A ratiometric fluorescent probe based on the FRET platform for the detection of sulfur dioxide derivatives and viscosity - Feng-Ting Liu; Peng-Fei Jiang; Yan-Pu Wang; Bao-Xiang Zhao; Zhao-Min Lin (Analytica Chimica Acta, 2024)

Anti-galvanic reaction induced interfacial engineering to reconstruct ternary colloid satellite platform for exceptionally high-performance redox-responsive sensor - Mei-huang Zeng; Qiu-hong Yao; Lin-min Chen; Chen Zhang; Jing-wen Jin; Ting-Xiu Ye; Xiao-mei Chen; Zhi-Yong Guo; Xi Chen (Analytica Chimica Acta, 2024)

Widely targeted metabolomic analysis reveals the dynamic changes of metabolites during postmortem chilled aging in Mongolian sheep - Min Zhang; Lina Sun; Rina Su; Mirco Corazzin; Zhihao Yang; Lu Dou; Guanhua Hu; Yue Zhang; Ting Liu; Yueying Guo; Lihua Zhao; Lin Su; et al. (Food Chemistry, 2024)

Impact of Pacific–Japan pattern on temperature and heatwave events in summer over Taiwan - Wan‐Ling Tseng; Szu‐Ying Lin; Yi‐Chi Wang; Shih‐How Lo; Min‐Hui Lo; Shih‐Yu Lee; Chieh‐Ting Tsai; Huang‐Hsiung Hsu (International Journal of Climatology, 2023)
The prediction of heatwave events is vital to provide information on possible hazards caused by extremely high temperature. The Pacific–Japan (PJ) pattern is a significant climate variability that controls the summer climate over East Asia. Previous studies have reported that the meridional propagating wave structure associated with the PJ pattern can modulate summer temperature and heatwave characteristics over northeast Asian countries, such as Korea and Japan. Nevertheless, its impacts on the subtropical regions, including Taiwan, a mountainous subtropical island with an approximate population of 24 million, is not yet fully understood. In this study, we investigate the impacts of the PJ pattern on the summer temperature and heatwave characteristics in Taiwan on the interannual timescale using long‐term station‐based temperature and rainfall dataset. We found an island‐wide increase in temperature during the positive phase of the PJ pattern, which is characterized by an anticyclonic anomalous circulation over Taiwan. Meanwhile, the averaged effective area and frequency of heatwave extremes over Taiwan have increased significantly, indicating an increase of exposure to heatwaves. Our examinations of large‐scale environment suggest that the adiabatic warming due to subsidence anomaly associated with the anticyclone over Taiwan is primary contributor of surface warming, which is balanced by diabatic cooling and meridional advective cooling on a seasonal timescale. Our study consolidated the links between the PJ pattern as a climate driver, hot summers and increased summer heatwave events over Taiwan. By combining with the seasonal prediction systems and early warning systems, such understanding can help sectors that are vulnerable to heat stress to prepare for potential hazards.

Inhibition of continuous cropping obstacle of celery by chemically modified biochar: An efficient approach to decrease bioavailability of phenolic allelochemicals - Chia-Chia Lin; Yu-Ting Liu; Po-Hsiang Chang; Yi-Cheng Hsieh; Yu-Min Tzou (Journal of Environmental Management, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

IoT-interfaced solid-contact ion-selective electrodes for cyber-monitoring of element- specific nutrient information in hydroponics - Yi-Min Wu; Shao-Yuan Liu; Bo-You Shi; Jui-Yu Peng; Zhi-Wei Kao; Yi-Yi Chen; Ting-Yu Hsieh; Hsing-Ying Chung; Chi-Yi Lin; Wei Fang; Lin-Chi Chen (Computers and Electronics in Agriculture, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Promotion of the catalytic polymerization of hydroquinone towards humic-like substances by graphitic carbon nitride - M.M.M. Ahmed; Yu-Ting Liu; S. Venkatesan; Min Chien Wu; Howida M. Nail; Der-Lii M. Tzou; Ming-Chang Lin; Kai-Yue Chen; Yu-min Tzou (Journal of Environmental Chemical Engineering, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Investigating the stretchability of doped poly(3-hexylthiophene)-block-poly(butyl acrylate) conjugated block copolymer thermoelectric thin films - Qing-Bao Zheng; Yan-Cheng Lin; Yen-Ting Lin; Yun Chang; Wei-Ni Wu; Jhih-Min Lin; Shih-Huang Tung; Wen-Chang Chen; Cheng-Liang Liu (Chemical Engineering Journal, 2023)

Sequential deacetylation/self-gelling chitin hydrogels and scaffolds functionalized with fucoidan for enhanced BMP-2 loading and sustained release - Hsien-Tsung Lu; Chi Lin; Yi-Ju Wang; Fang-Yu Hsu; Ju-Ting Hsu; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2023)

Growth-promoting and low-salt adaptation responses boosted by spermidine in Strombidium parasulcatum, a marine bacteriovorous ciliate potentially applied to live feeds for marine larviculture - Hung-Yun Lin; Bo-Ying Su; Nodali Ndraha; Sheng-Fang Tsai; Kuo-Ping Chiang; Hsin-Yun Liu; Yong-Ting Kang; Wei-Yu Yeh; Che-Chia Tsao; Yi-Min Chen; Hsin-I Hsiao; Han-Jia Lin (Aquaculture, 2023)

Inactivating Salmonella Enteritidis on shell eggs by using ozone microbubble water - Chia-Min Lin; Song-Yue Chen; Yi-Ting Lin; Chun-Ping Hsiao; Chih-Tung Liu; Sulfath Hakkim Hazeena; Jong-Shinn Wu; Chih-Yao Hou (International Journal of Food Microbiology, 2023)

Ultraviolet-based synergistic processes for wastewater disinfection: A review - Yi-Xuan Zhang; Jue-Lin Xiang; Jun-Jie Wang; Hai-Sheng Du; Ting-Ting Wang; Zheng-Yang Huo; Wen-Long Wang; Min Liu; Ye Du (Journal of Hazardous Materials, 2023)

Experimental Study on Fractal Characteristics of Surface Roughness of Briquettes and their Effect on Wettability of Coal Samples - Min Yan; Hanxi Luo; Ting Yang; Dongjie Yan; Jianing Wei; Haifei Lin; Shugang Li (Natural Resources Research, 2023)

Identification and Pathogen Stimulation Patterns of Neuronal Nitric Oxide Synthase (nNOS) in Black Rockfish (Sebastes schlegelii) - Xu Yan; Ningning Wang; Min Cao; Chao Li; Ning Yang; Ting Xue; Qiang Fu; Lin Song (Journal of Ocean University of China, 2023)

Retraction Note to: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2023)

Rab7a-mTORC1 signaling-mediated cholesterol trafficking from the lysosome to mitochondria ameliorates hepatic lipotoxicity induced by aflatoxin B1 exposure - Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Lin Che; Ting-Yu Li; Su-Min Mo; Dong-Bei Guo; Zhong-Ning Lin; Yu-Chun Lin (Chemosphere, 2023)

Removal and concurrent reduction of Cr(VI) by thermoacidophilic Cyanidiales: a novel extreme biomaterial enlightened for acidic and neutral conditions - Yen-Lin Cho; Yu-Min Tzou; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Shao-Lun Liu; Afifah Assakinah; Yu-Hsien Chen; Nhu Anh Thi Than; Yu-Ting Liu; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Transcriptomic data recover a new superfamily-level phylogeny of Cucujiformia (Coleoptera, Polyphaga) - Ming-Long Yuan; Wen-Ting Chen; Qi-Lin Zhang; Min Li; Li Zhang; Pei-An Tang (Molecular Phylogenetics and Evolution, 2023)

Activity concentrations and bioconcentration factors (BCFs) of natural radionuclides (40 K, 226Ra, and 232Th) from cultivated substrates to mushrooms - Wei-Hsiang Huang; Chih-Chung Lin; Yung-Yu Liu; Chao-Min Huang; Yi-Lung Yeh; Ting-Chien Chen (Environmental Science and Pollution Research, 2022)

Shallow-water hydrothermal vent system as an extreme proxy for discovery of microbiome significance in a crustacean holobiont - Ling Chiu; Min-Chen Wang; Kuang-Yu Tseng; Chih-Lin Wei; Huei-Ting Lin; Shan-Hua Yang; Yung-Che Tseng (Frontiers in Marine Science, 2022)
The shallow-water hydrothermal vent (HV) system off Kueishan Island lies at the end of the Okinawa Trough to the northeast of Taiwan. Near its submarine vent openings, aperiodic vent discharges generate a dynamic acidic (pH 5.5-8.1) and sulfidic (9-3000 μM) ecosystem. The dominant metazoan in this unique environment is the brachyuran vent crab, Xenograpsus testudinatus , which has developed robust metabolic strategies and highly adaptive acid-base regulatory mechanisms to maintain its physiological homeostasis. X. testudinatus is considered a holobiont, but the symbiotic mechanisms underlying acid and sulfur tolerance in the host-microbe system remain largely unclear. In this study, we used LoopSeq long-read sequencing of the full-length 16S rRNA gene to identify the bacterial communities present in the gills and carapace surface of X. testudinatus . The alpha diversity analysis, Venn diagram, and principal coordinate analysis (PCoA) indicated that the gills and carapace surface exhibit different bacterial constituents. Further measurements of relative abundance, coupled with functional predictions and fluorescence in situ hybridization (FISH), revealed a predominance of Sulfurovum sp. NBC37-1, a key bacterium that can perform sulfur and hydrogen oxidation to support denitrification processes. Consequently, our findings suggest that the symbiotic bacteria may play a critical role in conferring the extraordinary acid and sulfur tolerances of X. testudinatus , allowing the crustacean holobiont to thrive in its ecological niche within one of the most extreme marine habitats on Earth.

Fine particulate matter measured by satellites predicts the risk of age-related macular degeneration in a longitudinal cohort study - Chung-Ling Liang; Chi-Min Wang; Chau-Ren Jung; Ya-Chu Chang; Chun-Ju Lin; Yu-Ting Lin; Bing-Fang Hwang (Environmental Science and Pollution Research, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

The relationship between anthocyanin accumulation and photoprotection in young leaves of two dominant tree species in subtropical forests in different seasons - Zheng-Chao Yu; Wei Lin; Xiao-Ting Zheng; Wah Soon Chow; Yan-Na Luo; Min-Ling Cai; Chang-Lian Peng (Photosynthesis Research, 2021)

The major photoprotective role of anthocyanins in leaves of Arabidopsis thaliana under long-term high light treatment: antioxidant or light attenuator? - Xiao-Ting Zheng; Zheng-Chao Yu; Jun-Wei Tang; Min-Ling Cai; Yi-Lin Chen; Cheng-Wei Yang; Wah Soon Chow; Chang-Lian Peng (Photosynthesis Research, 2021)

Photosynthetic compensation of non-leaf organ stems of the invasive species Sphagneticola trilobata (L.) Pruski at low temperature - Min-ling Cai; Wen-qiao Ding; Jun-jie Zhai; Xiao-ting Zheng; Zheng-chao Yu; Qi-lei Zhang; Xiao-hua Lin; Wah Soon Chow; Chang-lian Peng (Photosynthesis Research, 2021)

Identification of miRNA targets in eggplant in response to Verticillium dahliae by degradome sequencing - Ting Li; Nianjiao Tao; Yuanmi Lin; Min Chen; Dongli Jiao; Chunmei Xue; Wenjiao Zhu; Qing Yang (European Journal of Plant Pathology, 2021)

Impact of Maternal Separation on Dopamine System and its Association with Parkinson's Disease - Kai-jie He; Yu-ting Zhang; Shi-zhuang Wei; Shu-min Jiang; Lin Xu; Chao Ren; Fen Wang (NeuroMolecular Medicine, 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Time-dependent shake map for Uttarakhand Himalayas, India, using recorded earthquakes - Himanshu Mittal; Yih-Min Wu; Ting-Li Lin; Cédric P. Legendre; Sushil Gupta; Benjamin M. Yang (Acta Geophysica, 2019)

G-CSF-primed haplo-identical HSCT with intensive immunosuppressive and myelosuppressive treatments does not increase the risk of pre-engraftment bloodstream infection: a multicenter case–control study - Jinhua Ren; Qiaoxian Lin; Weimin Chen; Congmeng Lin; Yuxin Zhang; Cunrong Chen; Shaozhen Chen; Xiaohong Yuan; Ping Chen; Xiaofeng Luo; Yun Lin; Lvying Shen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Dynamic monitoring of resuspension in the multiple eco-types of the littoral zone of a shallow wind-disturbed lake - Chuang Qi; Yang Zhou; Xiao-guang Xu; Li-min Zhang; Hui Lin; Xin-ting Wu; Kuan Shi; Guo-xiang Wang (Aquatic Sciences, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Occurrence and health risk assessment of organotins in waterworks and the source water of the Three Gorges Reservoir Region, China - Ting Deng; Lei Wu; Jun-Min Gao; Bin Zhou; Ya-Li Zhang; Wen-Nan Wu; Zhuo-Heng Tang; Wen-Chao Jiang; Wei-Lin Huang (Environmental Science and Pollution Research, 2018)

Antibacterial constituents from Antarctic fungus, Aspergillus sydowii SP-1 - Wen-ting Li; Dan Luo; Jia-ning Huang; Lin-lin Wang; Feng-guo Zhang; Tao Xi; Jian-min Liao; Yuan-yuan Lu (Natural Product Research, 2018)

A late Pleistocene marine glacial refugium in the south‐west of Hainan Island, China: Phylogeographical insights from the brown alga Sargassum polycystum - Zi‐Min Hu; Attachai Kantachumpoo; Ruo‐Yu Liu; Zhong‐Min Sun; Jian‐Ting Yao; Teruhisa Komatsu; Shinya Uwai; De‐Lin Duan (Journal of Biogeography, 2018)
Aim Hainan Island, southern China, is characterized by rich diversity and endemism of marine organisms, yet the underpinning mechanisms and processes contributing to speciation and diversification are poorly understood. Here, the brown alga Sargassum polycystum is used as a model to identify putative marine glacial refugia and explore biogeographical patterns driven by climate change in the late Pleistocene ice ages. Location South‐East Asia. Methods Mitochondrial cox1 and cox3 and nuclear internal transcribed spacer‐2 ( ITS 2) were obtained from 310, 325 and 313 individuals of S. polycystum (23 localities), respectively. Phylogenetic trees (maximum likelihood and Bayesian inference) and haplotype/ribotype networks were constructed to elucidate phylogeographical patterns. Analysis of molecular variance ( AMOVA ), neutrality tests (Tajima's D and Fu & Li's D* ), current (θ π ) and historical (θ w ) genetic diversities and extended Bayesian skyline plots ( EBSP ) were used to estimate historical demography. Results The populations from the south‐west of Hainan Island harboured much higher genetic diversity and unique endemism in comparison with other populations in the distribution range. Sargassum polycystum experienced relatively long‐term stable population size followed by a continued period of demographic expansion in the late Pleistocene. Main conclusions Our phylogeographical evidence revealed the existence of a previously unidentified marine refugium specific to S. polycystum in the south‐west of Hainan Island, China (the Central Depression of the Yinggehai Basin), along with a possible secondary refugium around the Bali Island, Indonesia. These biogeographical findings provide important insights regarding speciation, adaptation and evolution of marine organisms in South‐East Asia and the conservation of unique biodiversity under climate change.

RETRACTED ARTICLE: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2018)

Enhancement of simultaneous algicidal and denitrification of immobilized Acinetobacter sp. J25 with magnetic Fe3O4 nanoparticles - Jun feng Su; Dong hui Liang; Ting lin Huang; Li Wei; Min Ma; Jinsuo Lu (Environmental Science and Pollution Research, 2017)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

Surface Properties and In Vitro Bioactivity of Fluorapatite/TiO2 Coatings Deposited on Ti Substrates by Nd:YAG Laser Cladding - Chi-Sheng Chien; Yu-Sheng Ko; Tsung-Yuan Kuo; Tze-Yuan Liao; Huan-Chang Lin; Tzer-Min Lee; Ting-Fu Hong (Journal of Medical and Biological Engineering, 2015)

Development of an empirical model for rainfall-induced hillside vulnerability assessment: a case study on Chen-Yu-Lan watershed, Nantou, Taiwan - Tsu-Chiang Lei; Yi-Min Huang; Bing-Jean Lee; Meng-Hsun Hsieh; Kuan-Ting Lin (Natural Hazards, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

The Role of Pentacyclic Triterpenoids in the Allelopathic Effects of Alstonia scholaris - Chao-Min Wang; Hsiao-Ting Chen; Tsai-Chi Li; Jen-Hsien Weng; Yun-Lian Jhan; Shi-Xun Lin; Chang-Hung Chou (Journal of Chemical Ecology, 2014)

Shifts in microbial community composition and function in the acidification of a lead/zinc mine tailings - Lin‐xing Chen; Jin‐tian Li; Ya‐ting Chen; Li‐nan Huang; Zheng‐shuang Hua; Min Hu; Wen‐sheng Shu (Environmental Microbiology, 2013)
Summary In an attempt to link the microbial community composition and function in mine tailings to the generation of acid mine drainage, we simultaneously explored the geochemistry and microbiology of six tailings collected from a lead/zinc mine, i.e. primary tailings ( T 1), slightly acidic tailings ( T2 ), extremely acidic tailings ( T 3, T 4 and T 5) and orange‐coloured oxidized tailings ( T6 ). Geochemical results showed that the six tailings (from T 1 to T 6) likely represented sequential stages of the acidification process of the mine tailings. 16 S r RNA pyrosequencing revealed a contrasting microbial composition between the six tailings: P roteobacteria‐ related sequences dominated T 1– T 3 with relative abundance ranging from 56 to 93%, whereas F erroplasma‐ related sequences dominated T 4– T 6 with relative abundance ranging from 28 to 58%. Furthermore, metagenomic analysis of the microbial communities of T 2 and T 6 indicated that the genes encoding key enzymes for microbial carbon fixation, nitrogen fixation and sulfur oxidation in T 2 were largely from T hiobacillus and A cidithiobacillus , M ethylococcus capsulatus , and T hiobacillus denitrificans respectively; while those in T 6 were mostly identified in A cidithiobacillus and L eptospirillum , A cidithiobacillus and L eptospirillum , and A cidithiobacillus respectively. The microbial communities in T 2 and T 6 harboured more genes suggesting diverse metabolic capacities for sulfur oxidation/heavy metal detoxification and tolerating low pH respectively.

Differential distribution and activation of microglia in the brain of male C57BL/6J mice - Ting-Ting Yang; Chingju Lin; Chao-Tien Hsu; Tzu-Feng Wang; Fang-Yi Ke; Yu-Min Kuo (Brain Structure and Function, 2013)

Implications of the Up-regulation of Genes Encoding Protein Degradation Enzymes and Heat Shock Protein 90 for Intertidal Green Macroalga Ulva fasciata Against Hypersalinity-Induced Protein Oxidation - Ming-Shiuan Sung; Yuan-Ting Hsu; Kuan-Lin Ho; Tse-Min Lee (Marine Biotechnology, 2011)

Genes required for the functions of olfactory AWA neuron regulate the longevity of Caenorhabditis elegans in an insulin/IGF signaling-dependent fashion - Lu-Lu Shen; Min Du; Xing-Feng Lin; Ting Cai; Da-Yong Wang (Neuroscience Bulletin, 2010)

A Non-fluorescent Derivative from Derivatizing trans, trans-Muconic Acid with 2-(2-Naphthoxy)ethyl-2-(piperidino)ethanesulfonate - Tang-Chia Chung; Wung-Pung Su; Hwang-Shang Kou; Yu-Ting Lin; Min-Yuan Hung; Hsin-Lung Wu (Journal of Fluorescence, 2010)

Empirical Models to Predict Parsimoniously the Mass and Number Concentrations of Ultrafine Particulate in Ambient Atmosphere - Chia-Pin Chio; Man-Ting Cheng; Yu-Chi Lin; Chung-Min Liao (Bulletin of Environmental Contamination and Toxicology, 2009)

The distribution of HBV genotypes and clinical significance in familial clustering in an infected population with unfavorable prognosis - Jinfeng Liu; Yongqin Li; Tianyan Chen; Yuan Yang; Ke Wang; Yingli He; Qian Yang; Feng Ye; Yan Jin; Ting Qiu; Shumei Lin; Min Liu; et al. (Archives of Virology, 2008)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Mutation analysis of 218 Chinese patients with Wilson disease revealed no correlation between the canine copper toxicosis gene MURR1 and Wilson disease - Zhi-Ying Wu; Gui-Xian Zhao; Wan-Jin Chen; Ning Wang; Bo Wan; Min-Ting Lin; Shen-Xing Murong; Long Yu (Journal of Molecular Medicine, 2006)